Strategic Leadership Implementation and Corporate Performance - Obadina O M (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2024)
This study seeks to establish an empirical relationship between Strategic Leadership implementation and corporate performance the manufacturing firms in Nigeria. Quasi-experimental design was adopted with a structured questionnaire which was design for the generation of data from 115 respondents from the manufacturing firms in Nigeria. The Methodology for the study is quantitative and both descriptive and inferential statistics were utilised in the analysis of the data. Two null hypotheses that addressed the relationship between Strategic Leadership Implementation and the dimensions of Corporate Performance: cost Effectiveness and Market Share were tested in the study using Spearman’s rank order correlation coefficient at a 95% confidence interval and a 0.05 level of significance. The results revealed that Strategic Leadership Implementation significantly impacts all two measures of corporate performance, cost effectiveness and market share. As such all previous hypothetical statements were rejected as the findings revealed substantial levels of relationship between the variables. Based on the findings, the study therefore concluded that strategic leadership implementation has positive and significant relationship with cost effectiveness and market share in manufacturing firms in Nigeria.